Optical spectroscopic studies on GdF3:Tb3+,Yb 3+ nanocrystals - Guo, Y.; Cui, Z.; Jia, Guohua; Zhao, S.; Wang, H.; Deng, D.; Huang, L.; Xu, S. (2014)
Rare earth ions (Ln3+) doped optical materials manifest sharp and tunable emission, high photostability, long luminescent lifetime and low cytotoxicity, and find diverse applications in optics, optoelectronic devices and bio-labelling. Herein, we employed a conventional hydrothermal approach to control the size and tune the phase as well as the morphology of GdF 3:Tb3+,Yb3+ nanocrystals, wherein the effects of the synthetic conditions, such as pH, time, the ratio of the Gd to F and the surfactant, have been detailed investigated, producing sphere, platelet, rice, flower-shaped GdF3 nanoparticles. Diffuse reflectance spectra, photoluminescence emission and excitation spectra, and photoluminescence lifetime measurements were employed to characterize the optical spectroscopic properties of GdF3:Tb3+,Yb3+ nanocrystals. No efficient energy transfer from Tb3+ to Yb3+ is observed in GdF3:Tb3+,Yb3+ nanocrystals and the Yb 3+ shows a concentration quenching effect at high doping levels. © 2014 Elsevier B.V.